Hearing status of children under five years old in Jatinangor district - Wijana Wijana; Frino Abrianto; Shinta Fitri Boesoirie; Arif Dermawan (PERHATI-KL, 2020)
Background: Hearing is one of the most influential factors in children developmental process. The critical period of hearing and speech development begins in the first 6 months of life and continues until the age of 3 years. World Health Organization estimates that one to three in a thousand births have sensorineural hearing loss (SNHL). Early detection of hearing loss is substantial so that the diagnosis can be established and appropriate intervention can be done earlier. Purpose: To determine the hearing status in children under five years of age in Jatinangor. Method: A cross-sectional observational study with 240 subjects under the age of five in 12 Integrated Healthcare Center (Posyandu) in Jatinangor. Examinations included parental interviews, Behavioral Observation Audiometry (BOA), Otoacoustic Emissions (OAE), and tympanometry tests. Result: One child (0.4%) had moderate conductive hearing lossin the left ear, 1 child (0.4%) had bilateralsevere SNHL, and 7 children (2.9%) had profound bilateral SNHL. Conclusion: The incidence of hearing loss in children under five in Jatinangor was 3.8%, with bilateral profound SNHL asthe highest number, and the most common cause were prenatal Toxoplasma, Rubella, Cytomegalovirus (CMV) dan Herpes simplex virus (TORCH) infections.Keywords: children under-five, early detection, hearing status ABSTRAKLatar belakang: Pendengaran merupakan salah satu faktor yang sangat berpengaruh dalam proses perkembangan anak. Periode kritis perkembangan pendengaran dan berbicara dimulai dalam 6 bulan pertama kehidupan dan terus berlanjut sampai usia 3 tahun. Badan kesehatan dunia memperkirakan satu sampai tiga dalam seribu kelahiran terdapat kejadian gangguan dengar jenis sensorineural. Deteksi dini gangguan dengar penting untuk dilakukan sehingga diagnosis dapat ditegakkan dan intervensi yang tepat dapat dilakukan sedini mungkin. Tujuan: Untuk mengetahui status pendengaran pada anak usia bawah lima tahun di kecamatan Jatinangor. Metode: Penelitian observasional potong lintang dengan subjek penelitian 240 anak usia bawah lima tahun di 12 Pos Pelayanan Terpadu (Posyandu) Kecamatan Jatinangor. Dilakukan pemeriksaan meliputi wawancara orangtua anak, tes Behavioral Observation Audiometry (BOA), tes Otoacoustic Emissions (OAE) dan tes timpanometri. Hasil: Didapatkan 1 anak (0,4%) mengalami gangguan dengar konduktif derajat sedang pada telinga kiri, 1 anak (0,4%) mengalami gangguan dengar sensorineural derajat berat bilateral, dan 7 anak (2,9%) mengalami gangguan dengar sensorineural derajat sangat berat bilateral. Kesimpulan: Angka kejadian gangguan dengar pada balita di kecamatan Jatinangor sebesar 3,8% dengan gangguan dengar terbanyak berupa sensorineural derajat sangat berat bilateral, dan latar belakang penyebab terbanyak adalah infeksi prenatal Toxoplasma, Rubella, Cytomegalovirus dan Herpes simplex virus (TORCH).